Answer:
Option C is correct.
roots of the given equation ,
![x =(2\pm i√(26))/(3)](https://img.qammunity.org/2019/formulas/mathematics/high-school/gdbvgx2jrf7hbxavn3nrdiejolbx15cz6p.png)
Explanation:
Given the equation:
![3x^2+10 = 4x](https://img.qammunity.org/2019/formulas/mathematics/high-school/y1w71q9i5j7gr178f0cg675do20y20xn1m.png)
We can write this equation as:
![3x^2-4x + 10 =0](https://img.qammunity.org/2019/formulas/mathematics/high-school/jptri0in7tc0eqvnmro0llt3xrnxw9ccm4.png)
A quadratic equation is in the form of
......[1] where a,b ,c are the coefficient and x is the variable,
the solution of the equation is given by;
![x = (-b\pm√(b^2-4ac))/(2a)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/90cae1zsxigga291fbxbm9hhj3329rrsgc.png)
On comparing given equation with equation [1] we get;
a = 3 , b = -4 and c =10
So, the solution of the given equation is given by;
![x = (-(-4)\pm√((-4)^2-4(3)(10)))/(2(3))](https://img.qammunity.org/2019/formulas/mathematics/high-school/1icbvrp3u50mlplkw7e8aqy2f6uzhl64qt.png)
or
![x = (4\pm√((16-120))/(6) = (4\pm√((-104)))/(6) = (4\pm√((-4 * 26)))/(6)](https://img.qammunity.org/2019/formulas/mathematics/high-school/c1l541vbhe14y4y8ttevjwjhnj8ippfzu7.png)
or
[∴
![√(-1) = i](https://img.qammunity.org/2019/formulas/mathematics/college/chba0n82zu9nr4ca0bji42b0tr7gt0wnwh.png)
Simplify:
![x =(2\pm i√(26))/(3)](https://img.qammunity.org/2019/formulas/mathematics/high-school/gdbvgx2jrf7hbxavn3nrdiejolbx15cz6p.png)
therefore, the roots of the given equation are;
![x =(2\pm i√(26))/(3)](https://img.qammunity.org/2019/formulas/mathematics/high-school/gdbvgx2jrf7hbxavn3nrdiejolbx15cz6p.png)